2020
DOI: 10.1590/1980-265x-tce-2020-0002-0003
|View full text |Cite
|
Sign up to set email alerts
|

Data Integration in Mixed-Method Research Studies: Challenge and Opportunity for Nursing

Abstract: Mixed-method research studies have been referred to as those that condense, in the same study, procedures of collection, analysis, and combination/integration of data from quantitative and qualitative approaches/strands. To this end, the ascending paradigm upon mixed methods advocates that the assumption of integration between the approaches is one of the most elementary characteristics for considering the study as mixed, as well as it is what may mitigate the limitations of a single-method research study. 1 T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 5 publications
0
5
0
3
Order By: Relevance
“…15 In mixed methods research, a basic premise is the need for a clear integration between quantitative and qualitative results, as opposed to presenting research results in each arm separately 13 . Data integration, a crucial aspect in mixed methods research, is defined as a clear presentation of the association between the quantitative and qualitative arms 12,15 . The decision on how integration should take place depends on the study objectives, design, data collection and analysis strategies, as well as the researchers' experiences and skills.…”
Section: Mmat Criteria For Evaluating Mixed Methods Research Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…15 In mixed methods research, a basic premise is the need for a clear integration between quantitative and qualitative results, as opposed to presenting research results in each arm separately 13 . Data integration, a crucial aspect in mixed methods research, is defined as a clear presentation of the association between the quantitative and qualitative arms 12,15 . The decision on how integration should take place depends on the study objectives, design, data collection and analysis strategies, as well as the researchers' experiences and skills.…”
Section: Mmat Criteria For Evaluating Mixed Methods Research Studiesmentioning
confidence: 99%
“…Within the range of possibilities for scientific research in nursing lies the field of mixed methods research, which is made up of both quantitative and qualitative designs 11 . In this sense, mixed methods research has emerged as a new scientific paradigm which helps us to deepen our understanding about complex health issues for the betterment of human beings 10,12 . We recommend that, if reasonable and possible, nurse researchers opt for mixed methods research when examining and intervening in complex social and health problems.…”
Section: Introductionmentioning
confidence: 99%
“…Entende-se a fusão como um processo que demanda intensa abstração autoral e capacidade interpretativa avançada. 5 Já por incorporação, a integração acontece em projeto amplos, onde os dados são agrupados por conexão, construção e/ou fusão dentro das diferentes etapas do estudo. Para as propostas de fusão e incorporação, a estratégia analítica pode acontecer para orientar a sequência na coleta de dados e/ou apresentação e integração final dos dados.…”
Section: Tabela Falante: Estratégia Analítica Em Métodos Mistosunclassified
“…No campo da enfermagem, essa abordagem vem crescendo à medida que os objetos de estudo, nesse cenário científico, são imbuídos de maior densidade de informações e significados, o que requer abordagens integradoras. 5 A definição da abordagem mista não deve partir de escolha pessoal dos pesquisadores, mas deve representar com profundidade e compreensão os problemas de pesquisa e objetos estudados, que emanam a exigência e conduzem à integração metodológica. Para contextualizar o estudo aqui relatado, a realidade do objeto exigia quantificar e caracterizar situações (condições de saúde crônicas e agudas), bem como identificar e compreender como funcionam as Redes de Atenção à Saúde, partindo do pressuposto de demandas crônicas e agudas de saúde de recém-nascidos prematuros moderados e tardios no primeiro ano de vida.…”
Section: Introductionunclassified
“…In nursing, this approach has been growing as the objects of study, in this scientific scenario, are imbued with a greater density of information and meanings, which requires integrative approaches. 5 The mixed approach definition should not come from the researchers' personal choice, but should represent in depth and understanding the research problems and objects studied, which emanate from the requirement and lead to methodological integration. To contextualize the study reported here, the reality of the object required quantifying and characterizing situations (chronic and acute health conditions), as well as to identify and understand how Health Care Networks work, based on the assumption of chronic and acute health demands of moderate and late preterm newborns in the first year of life.…”
Section: Introductionmentioning
confidence: 99%